2018
DOI: 10.1007/s00127-018-1524-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant use in adolescents in northern Russia

Abstract: PurposeTo determine the prevalence of inhalant use in Russian adolescents and to investigate associated psychosocial problems from a gender perspective.MethodsData on inhalant use and comorbid psychopathology were collected by means of self-reports from 2892 (42.4% boys) sixth to tenth grade students in public schools in Arkhangelsk, Russia. Multivariate analysis of covariance was used to assess differences in the levels of internalizing and externalizing problems in boys and girls, who were non-users and user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Penggunaan zat inhalen (lem aibon) adalah umum di kalangan remaja 6 .Banyak hal yang masih bisa dilakukan dan membantu remaja yang sudah terjerumus penyalahgunaan menghirup lem aibon, salah satunya adalah dalam bentuk pendidikan, penyebaran informasi mengenai bahaya menghirup lem aibon, pendekatan melalui keluarga, dll 7 .Kurangnya pengetahuan dapat diperbaiki dengan cara pemberian edukasi terstruktur atau pendidikan kesehatan dan pendampingan tentang NAPZA 8 . Pendidikan kesehatan dalam arti pendidikan.…”
Section: Metode Pelaksanaanunclassified
“…Penggunaan zat inhalen (lem aibon) adalah umum di kalangan remaja 6 .Banyak hal yang masih bisa dilakukan dan membantu remaja yang sudah terjerumus penyalahgunaan menghirup lem aibon, salah satunya adalah dalam bentuk pendidikan, penyebaran informasi mengenai bahaya menghirup lem aibon, pendekatan melalui keluarga, dll 7 .Kurangnya pengetahuan dapat diperbaiki dengan cara pemberian edukasi terstruktur atau pendidikan kesehatan dan pendampingan tentang NAPZA 8 . Pendidikan kesehatan dalam arti pendidikan.…”
Section: Metode Pelaksanaanunclassified
“…Other drugs, including Ecstasy and other amphetamines, were not widely used. A survey of sixth to tenth grade students in public schools in Arkhangelsk, Koposov, Stickley and Ruchkin (2018) found that 6.1 percent of boys and 3.5 percent of girls reported use of inhalants (N = 2892). In an attitude study of university students in Smolensk (N = 150), it was found that the students had mostly negative attitudes toward drug users and that many regarded drug users as "weak, stupid, unreliable, and unhappy" (Gritsenko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mostly the fox glue users are those who have a low economy (Kalra, 2018;Koposov et al, 2018;Pitoyo & Kurniawan, 2021;Vázquez et al, 2019), especially teenagers who work on the streets (Jhakar et al, 2017;Lakshmana, 2019;Sah et al, 2020). Working hours on the streets are tiring and draining, prompting teenagers to try using affordable fox (Dhawan et al, 2020;Masud & Khan, 2018).…”
Section: Introductionmentioning
confidence: 99%